Diet and Skin Cancer: The Potential Role of Dietary Antioxidants in Nonmelanoma Skin Cancer Prevention - Rajani Katta; Danielle Nicole Brown (Journal of Skin Cancer)
Nonmelanoma skin cancer (NMSC) is the most common cancer among Americans. Ultraviolet (UV) radiation exposure is the major risk factor for the development of NMSC. Dietary AOs may prevent free radical-mediated DNA damage and tumorigenesis secondary to UV radiation. Numerous laboratory studies have found that certain dietary AOs show significant promise in skin cancer prevention. These results have been substantiated by animal studies. In human studies, researchers have evaluated both oral AO supplements and dietary intake of AOs via whole foods. In this review, we provide an overview of the role of AOs in preventing tumorigenesis and outline four targeted dietary AOs. We review the results of research evaluating oral AOs supplements as compared to dietary AOs intake via whole foods. While these specific supplements have not shown efficacy, intake of AOs via consumption of whole foods has shown some promise. Lessons learned from the field of hypertension research may provide important guidance in future study design. Further research on the role of dietary AOs in the prevention of NMSC is warranted and should focus on intake via whole food consumption.